Efektivitas Pengembangan Nilai Karakter Siswa dengan Menciptakan Program Sekolah Ramah Anak - Faizatul Widat; Fathor Rozi; Moh. Kholili (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
Making students with character is a form of educator responsibility whose essence is to develop a complete human being in the field of morality, namely a human being with nature. Child-friendly education programs implemented in schools directly or indirectly will shape the morals or character of the students at the school. This study aims to analyze and understand the effectiveness of developing character values ​​by creating a child-friendly school program at MI Tarbiyatul Islam. This study uses a qualitative approach to the type of case study. The results of the study show that, firstly, the development of character values ​​is being encouraged at MI Tarbiyatul Islam. Second, the development of character values ​​by creating child-friendly schools has been carried out in the following ways; Swot Analysis, SRA Implementation, and Continuous Improvement. The implications obtained by making the child-friendly school program at MI Tarbiyatul Islam develop character values ​​for students are getting higher with mutual respect, mutual assistance, and high empathy, so that character values ​​are formed early on